Resistance and interculturality - SANDOVAL HERNÁNDEZ, Federico (Utopía y Praxis Latinoamericana, 2025)
Resistance is considered intercultural, within a territorial space determined by the locality and the Mesoamerican cultural region, over a long period of time. Therefore, Chontal culture is not univocal, as it exists within a context of globality and with actions promoting compatibility. Socioeconomics, agroecology, and geopolitics go hand in hand with interculturality, with a historical and theoretical methodological basis, proposing some reflections on the compatibility of local and global knowledge, where diachrony and synchrony go hand in hand with the locality of San Andrés Tuxpan, that is, from the pre-Hispanic to the current, without neglecting the viceregal period. This allows for some general conclusions to be drawn for contemporary analysis with glocal survival strategies, such as conservation zones, education, experimentation, community-rooted identity, and the implementation of alternative programs.